Market power and wage inequality - Shubhdeep Deb; Jan Eeckhout; Aseem Patel; Lawrence Warren (Institute for Fiscal Studies (IFS), 2022)
We propose a theory of how market power affects wage inequality. We ask how goods and labor market power jointly affect the level of wages, the Skill Premium, and wage inequality. We then use detailed microdata from the US Census between 1997 and 2016 to estimate the parameters of labor supply, technology and the market structure. We find that a less competitive market structure lowers the wage level, contributes 7% to the rise in the Skill Premium and accounts for half of the increase in between-establishment wage variance.
Keywords: C6; D3; D4; D5; L1; 330; Market Power; Wage Inequality; Skill Premium; Technological Change; Market Structure; Endogenous Markups; Endogenous Markdowns